2016
DOI: 10.22180/na174
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous Nitrogen-Doped Carbon Nanofibers as Efficient Metal-Free Catalysts toward the Electrocatalytic Oxygen Reduction Reaction

Abstract: Citation: Y. Chen, Q. Liu and J. Wang, Nano Adv., 2016, 1, 79−89.Activated N-doped carbon nanofibers (ANCNFs) were successfully prepared by the combination of electrospinning and following chemical activation of polyacrylonitrile (PAN) as metal-free electrocatalysts for oxygen reduction reaction (ORR). The increase in the activation temperature leads to not only increased specific surface areas and pore volume, and larger percentage of microporosity, but also the gradual loss of nitrogen and continuous increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…In contrast, the percentage of graphitic-N increased from 49.60% for OMNC-800 to 53.96% for OMNC-800A. These findings are consistent with the fact that graphitic N is more stable than pyridinic N. 39 In general, pyridinic N and graphitic N in carbons are regarded as electroactive sites, which would benefit the enhancement of electrical conductivity as well as capacitances. 40,41 Based on the analysis of N 2 adsorption-desorption isotherms ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…In contrast, the percentage of graphitic-N increased from 49.60% for OMNC-800 to 53.96% for OMNC-800A. These findings are consistent with the fact that graphitic N is more stable than pyridinic N. 39 In general, pyridinic N and graphitic N in carbons are regarded as electroactive sites, which would benefit the enhancement of electrical conductivity as well as capacitances. 40,41 Based on the analysis of N 2 adsorption-desorption isotherms ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…In contrast, PC showed a type-I isotherm (Fig. 5 a), which is a typical of microporous materials [ 13 , 51 53 ]. The BET surface areas ( S BET ) for NC-1, NC-3, and NC-6 were 22, 80, and 86 m 2 g −1 , respectively, which was much lower than the S BET of PC (529 m 2 g −1 ), as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…ENFs-based materials for high surface area and better mass transfer property. To date, various strategies have been reported to successfully realize the desired porous structure, which mainly includes: hard-template methods (e.g., Si nanoparticles), [66] soft-template methods, [67] chemical activation (e.g., KOH) [68] and ultralow-oxygen-etching, [69,70] etc. Besides, CO 2 and water vapor also act as activating agents to generate porous structure of ECNFs-based materials.…”
Section: Porous Structure Of Individual Nanofibersmentioning
confidence: 99%
“…The activation parameters (e.g., activation temperature and amount of KOH) have an important influence on the catalytic performance. Wang et al [68] reported activated N-doped CNFs (ANCNFs) by the combination of electrospinning and following KOH activation at elevated temperature. They found that the BET surface area of the resultant ANCNFs increased with the rise of the activation temperature.…”
Section: N-doped Ecnfsmentioning
confidence: 99%
See 1 more Smart Citation